2004
DOI: 10.1111/j.1600-0765.2004.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative activities of epithelial and connective tissue cells in the rat periodontal regeneration using argyrophilic nucleolar organizer regions staining

Abstract: These results imply that long junctional epithelium cannot supply sufficient epithelial cells because of their significantly low rates of proliferation, consequently long junctional epithelium becomes shorter after 12 weeks, whereas the proliferative activity of regenerative connective tissue maintains the same level of proliferation, and ultimately long junctional epithelium is replaced by regenerative connective tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
1
0
1
Order By: Relevance
“…All study groups showed a degree of epithelial downgrowth when considering normal structure. This is known to be a common finding in periodontium being regenerated after loss (Usuda et al, 2004). However, our results showed more favorable results with P 11 -4 as shown by the significant decrease in epithelial downgrowth after 4 weeks in the P 11 -4 treated group.…”
Section: Discussioncontrasting
confidence: 44%
“…All study groups showed a degree of epithelial downgrowth when considering normal structure. This is known to be a common finding in periodontium being regenerated after loss (Usuda et al, 2004). However, our results showed more favorable results with P 11 -4 as shown by the significant decrease in epithelial downgrowth after 4 weeks in the P 11 -4 treated group.…”
Section: Discussioncontrasting
confidence: 44%
“…However, recent investigations using autoradiography demonstrated that a significant number of DAT cells are capable of synthesizing DNA, as do basal cells along the connective tissue (9, 10). The results of our previous studies using argyrophilic nucleolar organizer region (AgNORs) staining also support the idea that DAT cells have proliferative activity (20, 21).…”
Section: Discussionsupporting
confidence: 78%